Improving Students’ Ability in Writing Scientific Papers Through Process Approach - Fitri Ayu; Devi Anggriani; Nizamuddin (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
One of the writing skills that must be mastered by intellectuals is writing scientific papers. The Indonesian curriculum covers all language skills, including writing. The curriculum is described in the Competency Standards and Basic Competencies (SK and KD) from elementary to high school levels. This study aims to determine the ability of students in class XII MIA 4 SMA Panca Budi in writing scientific papers that will be useful for continuing their education to the university level. This research was conducted as a solution offer that would guide these students to write using an approach, namely "Process Approach". The results showed a significant increase in the ability to write scientific papers. This is proven by the movement of students' average writing scores from 63.10 during the pre-test, to 73.13 during the test in cycle 1 and increased again to 88.82 in the test in cycle 2. In other words, the process approach has been proven to be able to improve the ability to write scientific papers of students, especially students of grade XII MIA 4 SMA Panca Budi.